Unidades de actuación urbanística o gestión: casos de aplicación en tres planes parciales de Bogotá D.C. (2017)
The results of the comparison of three partial plans formulated for the development and urban renewal of different areas of the city of Bogotá are presented. Emphasis is placed on the two forms of application of management instruments: urban action units and management units. The specific circumstances that explain the implementation of each of these tools in the comparative plans are analyzed. It also describes how the first figure operates when there are reluctant owners, and how the second works if there is full consensus for the allocation of charges and benefits among these.